Prova documental eletrônica no processo do trabalho: validade e valoração - Ferreira Neto, Arthur Leopoldino (2017)
The indisputable current essentiality of the internet, with the information technology revolution, has brought a radical change in legal relationships, both in the form of data storage and information exchange, and in the conduct of judicial processes. We can see nowadays a significant change in legal relationships, since the records that were previously made on paper, are now carried out digitally, through electronic documents. This facility raises some troubling points. Among them, the credibility of the electronic document because of its abstract support in the face of the material support of the traditional document. Another point is: is the technology nowadays enough that we can equip it with the traditional document? We can not forget that security is the main fear of those who use electronic means. The reliability of electronic documents is associated with the conviction that it has not been adulterated in the path between sender and receiver, and that its author subscribes. This is the panorama on which the problem of this work is based, so that electronic evidence can be given probative force